Feasibility of minimally invasive management in patients with forgotten double J stent: a single centre experience - Ahmed, Mohd Hamid Shafique; Toshniwal, Harshad; Pawar, Prakash W.; Sawant, Ajit S.; Arora, Amandeep; Abbas, Syed Ali; Sakharani, Jitendra K.; Shah, Neel (International Journal of Research in Medical Sciences, 2019)
Background: aim of the study was to present the experience in managing forgotten/encrusted Double J (DJ) ureteral stents and to review the literature on the subject. Methods: Author retrospectively studied patients presenting to the Outpatient Department from January 2016 to January 2019 with forgotten DJ stent(s) (six or more than six months after the insertion). Data was collected for age, gender, indication for DJ stenting, clinical features at presentation, radiological imaging and surgical procedure performed to extract the DJ stents. The post-operative stay, complications of the procedures and morbidity was also studied. Results: During the study period, a total 32 patients reported to the department with history of forgotten DJ stents. Most common age group involved was 41-60 years. Most common presenting symptoms were lower urinary tract symptoms (LUTS) or dysuria. Duration of stent in-situ ranged from 6 month to 15 years. Most common sites of encrustations along the forgotten DJ stent were ureter and kidney followed by urinary blabber. Fluoroscopic guided DJ stent removal was done in 8 patients. A combination of Cystolithotripsy, URSL and PCNL was needed to clear the stone and extract the DJ stent in remaining patients. Conclusions: Forgotten/encrusted DJ stent may lead to complications ranging from urinary tract infections to loss of renal function. They can be safely and successfully removed, and the renal function can be preserved. Endo-urological management of forgotten encrusted stents is highly successful and often avoids the need for open surgical techniques.